2020
DOI: 10.1186/s12894-020-00690-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microhematuria in renal colic and urolithiasis: a systematic review and meta-analysis

Abstract: Background: This systematic review and meta-analysis aims to investigate the prevalence of microhematuria in patients presenting with suspected acute renal colic and/or confirmed urolithiasis at the emergency department. Methods: A comprehensive literature search was conducted to find relevant data on prevalence of microhematuria in patients with suspected acute renal colic and/or confirmed urolithiasis. Data from each study regarding study design, patient characteristics and prevalence of microhematuria were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In our study, we also evaluated these parameters. Hematuria, a parameter that can be considered as stone-specific, shows a very high prevalence in patients with renal colic [ 24 ]. In our study, although there was a significant difference between groups in paired comparisons, we observed that 10 patients with LBP had microscopic hematuria without significant findings on CT or US, and this hematuria disappeared after symptomatic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we also evaluated these parameters. Hematuria, a parameter that can be considered as stone-specific, shows a very high prevalence in patients with renal colic [ 24 ]. In our study, although there was a significant difference between groups in paired comparisons, we observed that 10 patients with LBP had microscopic hematuria without significant findings on CT or US, and this hematuria disappeared after symptomatic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although there was a significant difference between groups in paired comparisons, we observed that 10 patients with LBP had microscopic hematuria without significant findings on CT or US, and this hematuria disappeared after symptomatic treatment. In their meta-analysis, Minotti et al also emphasized that microhematuria was not sufficient to be a stone-specific symptom [ 24 ]. Again, it is remarkable that nausea-vomiting, which is thought to develop secondary to tension in the kidney capsule and hydronephrosis, was not observed in most of our patients, but was seen in a small number of patients with LBP.…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly accompanied by NVH, but VH may be seen. It is worth noting that up to 10–30% of stones (number varies by report) are not associated with haematuria, despite confirmed radiological evidence of stone disease (Minotti et al., 2020).…”
Section: Common Causes Of Haematuria (Upper and Lower Tract)mentioning
confidence: 99%
“…They are commonly accompanied by NVH, but VH may be seen. It is worth noting that up to 10-30% of stones (number varies by report) are not associated with haematuria, despite confirmed radiological evidence of stone disease (Minotti et al, 2020). The management of stone disease is complex, with several factors determining management (either on an emergency, or urgent outpatient basis).…”
Section: Urolithiasis (Urinary Tract Stones)mentioning
confidence: 99%
“…This can result from a prerenal cause, such as dehydration (in case of vomiting), or from a postrenal cause, such as unilateral or bilateral obstruction. Unilateral obstruction in patients with solitary kidney and bilateral obstruction are responsible for higher creatinine levels [12,13]. Another important analysis is the serum calcium.…”
Section: Blood Testmentioning
confidence: 99%